Developing a Book Creator-Based Interactive E-Module to Enhance Numeracy and Green Economy Awareness Among Elementary Students - Ratih Purnamasari; Nurlinda Safitri; Rukmini Handayani; Siti Maysarah; Ilham Abdulrahman (STAI Hubbulwathan Duri, 2025)
Integrating sustainability themes into mathematics education can enhance both cognitive and environmental competencies. This study aimed to develop and evaluate an interactive e-module using Book Creator that combines fraction-ordering concepts with green economy themes to improve elementary students’ numeracy skills and environmental awareness. The module was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and featured multimodal content including text, visuals, video narration, and interactive tasks designed for fifth-grade learners. A limited trial was conducted with 75 students from a public elementary school in Indonesia. Expert validation and a pretest–posttest design were used to assess feasibility and learning outcomes. Expert validation indicated excellent feasibility in content (97.9%), media (96%), and language (98%). Student responses showed high engagement and perceived usefulness (average score: 88.6%). Quantitative analysis revealed a moderate increase in numeracy skills, with an average N-gain of 0.597. Qualitative observations indicated improved understanding, enthusiasm, and active participation. The findings demonstrate that interactive, contextually relevant digital modules can effectively support numeracy development and environmental education. Grounded in Piagetian and Vygotskian principles, the module encourages concrete operational thinking and social learning. Its digital format allows for flexible integration in both blended and remote learning settings. The Book Creator-based module offers promising pedagogical value for integrating mathematics and sustainability in primary education. Future studies should investigate broader application and long-term impacts on student learning and behavior.